Edge of Eternity - Follett, Ken; Lee, John Rafter; Penguin Audio (Firm) (New York : Penguin Audio, 2014)
The conclusion to Ken Follett's historical series that follows the fortunes of five intertwined families, American, German, Russian, English, and Welsh, through the twentieth century. Now they come to one of the most chaotic eras of all: the enormous social, political, and economic turmoil of the 1960s through the 1990s, from civil rights, assassinations, mass political movements and Vietnam to the Berlin Wall, the Cuban Missile Crisis, presidential impeachment, revolution, and rock and roll.
Keywords: World politics -- Fiction -- 1945-1989; Political fiction; Historical fiction; Spy stories; Audiobooks